Jerusalem and Judaism - Jodock, Darrell 1941- (2020)
The image of Jerusalem is a key component of both historical and contemporary Judaism. Beyond the struggle for territory and space, it is also about the involvement of God in history and in the world. This is something that can parallel Christian understandings, and might be a place for Christians and Jews to engage in fruitful discussions and understandings.
Keywords: Land (Jewish theology); Incarnation; Christianity and Judaism; Eschatology - Judaism; Zionism; Judaism and state; Judaism and politics; Jerusalem